Some Hypotheses about Copper Mining Reforms - Pásara, Luis (1974)
The article analyzes the reforms in copper mining in Peru, highlighting the importance of the exploitation of unused resources, the reversion of concessions to private companies and state participation in mining exploitation, as well as the participation of workers in the sector. In this regard, the author questions the effectiveness of the reforms and their actual implementation, due to the persistence of economic dependence, the continued presence of foreign companies in copper exploitation and the mediating or regressive translation of political objectives into concrete implementation measures. In this framework, the need for a renegotiation with imperialism in order to maximize national benefits and the redefinition of the national economy is suggested. The author highlights the persistence of certain nationalist values that may not be contributing effectively to the maximization of national benefits. In addition, he discusses the implementation of the new mining policy in Peru, highlighting the reversion of mining concessions, state exploitation and commercialization by the state. Finally, the need for detailed research to understand the direction and impact of the presence of foreign companies in state copper exploitation is discussed.